Bio‐inspired dicalcium phosphate anhydrate/poly(lactic acid) nanocomposite fibrous scaffolds for hard tissue regeneration: In situ synthesis and electrospinning. Issue 2 (7th August 2013) - Chae, Taesik; Yang, Heejae; Ko, Frank; Troczynski, Tom
Abstract The fundamental building blocks of hierarchically structured bone tissue are mineralized collagen fibrils with calcium phosphate nanocrystals that are biologically "engineered" through biomineralization. In this study, we demonstrate an original invention of dicalcium phosphate anhydrate (DCPA)/poly(lactic acid) (PLA) composite nanofibers, which mimics the mineralized collagen fibrils via biomimetic in situ synthesis and electrospinning for hard tissue regenerative medicines. The interaction of the Ca2+ ions and the carbonyl groups in the PLA provides nucleation sites for DCPA during the in situ synthesis process. This resulted in the improved dispersion of DCPA nanocrystallites in the intrananoporous PLA nanofibers through electrospinning, compared to the severely agglomerated clusters of DCPA nanoparticles fabricated by conventional mechanical blending/electrospinning methods. The addition of poly(ethylene glycol), as a copolymer source, generated more stable and efficient electrospun jets and aided in the electrospinability of the PLA nanofibers incorporating the nanocrystallites. It is expected that the uniformly distributed DCPA nanocrystallites and its unique nanocomposite fibrous topography will enhance the biological performance and the structural stability of the scaffolds used for hard tissue reconstruction and regeneration. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 514–522, 2014.